Negative traits, positive assortment: Revisiting the Dark Triad and a preference for similar others. (April 2021) - Kay, Cameron S.
Across two studies ( N TOTAL = 933), a person's willingness to engage in a relationship with those scoring high in each of the Dark Triad traits (i.e., Machiavellianism, narcissism, and psychopathy) was examined as a function of their own levels of the Dark Triad traits and the relationship type in question (i.e., a one-night stand, a dating relationship, or a marriage). There were three notable findings. First, those scoring high in Machiavellianism, narcissism, and psychopathy were more willing to engage in a relationship with a person who was also high in Machiavellianism, narcissism, and psychopathy, respectively. Second, as the commitment level of the relationship increased, so did a narcissistic individual's willingness to engage in a relationship with a fellow narcissist. Third, psychopathic people were generally interested in having one-night stands, seemingly without concern for the personality traits of the other person involved. Results are discussed in relation to assortative mating.